Ways of reading and constructing the space in the novel Niebla by Miguel de Unamuno. - Campos, Alexandre Silveira [UNESP] (Univ Estadual Paulista-unesp, 2015)
This paper discusses how the proposal of some fundamentals concepts applied to the analysis of the space in literary works such as nature, scenery, landscape and territory can be used for a dialectical and critical reading of important dichotomies found in the novel Niebla by Miguel de Unamuno such as province/metropolis, country/city and nature/society.
Keywords: Niebla; Miguel de Unamuno; The space in literature; Topoanalysis